Wear and corrosion characteristics of electroless Ni–W–P–B4C and Ni–P–B4C coatings. (September 2014) - Araghi, A.; Paydar, M. H.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, the microhardness, wear and corrosion resistance of electroless deposited Ni–W–P–B4C, Ni–P–B4C, Ni–W–P and Ni–P coatings on AZ91D magnesium alloy were investigated. The hardness of the Ni–W–P–B4C and Ni–P–B4C composite coatings was more than that of the Ni–P and Ni–W–P coatings. The Pin on disk wear test results showed that the Ni–W–P–B4C and Ni–P–B4C composite coatings have a better wear resistance in comparison to the Ni–W–P and Ni–P coatings. The worn surfaces exhibited a change in the wear mechanism from adhesive for the Ni–P coating to abrasive for the Ni–W–P and Ni–W–P–B4C coatings and combination of adhesive and abrasive for the Ni–P–B4C composite coating. Tafel test has been used to assess corrosion performance of the specimens; the Ni–W–P coatings exhibited the best corrosion resistance while the Ni–W–P–B4C and Ni–P–B4C composite coatings showed less corrosion performance than the Ni–W–P and Ni–P coatings respectively.